2015
DOI: 10.3153/jaefr16001
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Cyprinus Carpio Fingerlings Fed Diets Containing Hydrothermally Processed Citrullus Lanatus Seed Meal

Abstract: Abstract:The effect of incorporating hydrothermally processed watermelon whole seeds in the diet of fish was investigated on growth, feed utilization and body composition of carp (Cyprinus carpio) fingerlings. Fish diets (35% crude protein) were formulated using water melon hydrothermally processed for 0 (DT1), 10 (DT2), 20(DT3), 30 (DT4) and 40 minutes (DT5) boiling time. Twenty fingerlings (1.50±0.00g each) were randomly allocated in triplicate to 70 liters plastic bowls, for each treatments, aeration was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…This result is similar to the results of Bello et al (2013), Shazali et al (2013) and who reported on fish fed diets of walnut leaves, onion bulb residues and watermelon seed meal, respectively. The values obtained in this study were higher than values reported by Tiamiyu et al (2016) on Orechromis niloticus fed Moringa oleifera leaf meal. However, this variation may be attributed to the replacement nature.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…This result is similar to the results of Bello et al (2013), Shazali et al (2013) and who reported on fish fed diets of walnut leaves, onion bulb residues and watermelon seed meal, respectively. The values obtained in this study were higher than values reported by Tiamiyu et al (2016) on Orechromis niloticus fed Moringa oleifera leaf meal. However, this variation may be attributed to the replacement nature.…”
Section: Discussioncontrasting
confidence: 90%
“…However, this variation may be attributed to the replacement nature. In the study by Tiamiyu et al (2016), soybean was replaced with Moringa oleifera leaf meal weight for weight while the present study replaced crude protein for crude protein. The study further revealed that feed conversion ratio, specific growth rate and protein efficiency ratio of the fish fed experimental diets were improved compared to the fish fed control diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the result of this study, Tiamiyu et al [20] demonstrated that boiling watermelon seed up to 40 min did not affect the protein content or feed utilization by C. gariepinus. However, a feeding trial with Cyprinus carpio showed a significant reduction in performance beyond 30 min of hydrothermal processing [21].…”
Section: Discussionmentioning
confidence: 95%